La révocation d'un agent et le statut d'intermédiaire de commerce - L’Heureux, Nicole (Les Cahiers de droit, 1977)
The revocation of an agent frequently raises the question of the legal basis for the right to indemnity by agent so revoked. The existence of such a right as well as the determination of the amount of the indemnity depend on the nature of the relationship between the agent and his client. In the case of an independent agent, this relationship is of a special nature. His function differs from that of a servant and that of an independent trader, who are both currently called agents. The indépendant agent deals with third parties for a client, but does not himself supply the goods and services in which he trades. The indépendant agent, to whom is recognized the status of commercial intermediary, has a function which is characterized by his own obligational contents. He brings to the execution of his work the duties of a professional. He is subject to an obligation of diligence and, because of his professional status, incurs a certain liability towards the third party he deals with. The qualification of mandate, often given to his contract, cannot take into account the extensive obligations imposed on the agent, particularly the fact that he makes a profession of his agency and that he has a special interest in the success of the affair he négociâtes. The reference to rules of a civil nature in matters that relate to business creates some confusion. The nature of the relationship between the agent and his client is challenged by the notion of common interest which grants to the agent a right to keep up the contract and maintain goodwill. The proposition of the Civil Code Revision Office for the revision of the legal categories has the advantage of giving new definitions to contracts which are characterized by the autonomy of the obligee in the execution. In the case of the independent agent, it will favour a qualification more adequate of the relationship between him and his client. The revocation of the agent would then be treated like the revocation in other contracts in which work is done in the interest of the other party.